2019
DOI: 10.1007/s10551-019-04123-w
|View full text |Cite
|
Sign up to set email alerts
|

‘Alternative Hedonism’: Exploring the Role of Pleasure in Moral Markets

Abstract: Fair trade', 'ethical' and 'sustainable' consumption emerged in response to rising concerns about the destructive effects of hedonic models of consumption that are typical of late capitalist societies. Advocates of these 'markets for virtue' sought to supplant the insatiable hedonic impulse with a morally restrained, self-disciplining disposition to consumption. With moral markets currently losing their appeal, we respond to the tendency to view hedonism as an inhibitor of moral market behaviour, and view it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
0
29
0
1
Order By: Relevance
“…For example, we found that for MDMA and/or mephedrone users, motivation tended to centre on individual factors like pleasure, experimentation and curiosity, as well as factors linked to social cohesion solidified through networks and relationships. We framed this as 'hedonist' usage, which we acknowledge is a morally contentious term by some academics (Caruana, Glozer, & Eckhardt, 2019;Wakeman, 2016). Yet the concept of 'hedonism' nevertheless conveys how these participants were focused on positive outcomes of ATS use and the cementing of social networks, legitimated through 'self-managing' strategies (Caruana et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we found that for MDMA and/or mephedrone users, motivation tended to centre on individual factors like pleasure, experimentation and curiosity, as well as factors linked to social cohesion solidified through networks and relationships. We framed this as 'hedonist' usage, which we acknowledge is a morally contentious term by some academics (Caruana, Glozer, & Eckhardt, 2019;Wakeman, 2016). Yet the concept of 'hedonism' nevertheless conveys how these participants were focused on positive outcomes of ATS use and the cementing of social networks, legitimated through 'self-managing' strategies (Caruana et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We framed this as 'hedonist' usage, which we acknowledge is a morally contentious term by some academics (Caruana, Glozer, & Eckhardt, 2019;Wakeman, 2016). Yet the concept of 'hedonism' nevertheless conveys how these participants were focused on positive outcomes of ATS use and the cementing of social networks, legitimated through 'self-managing' strategies (Caruana et al, 2019). This group tended to recover from and 'mature out' of using ATS (Levy, Arria, O'Grady, & Wish, 2005), as they accrued additional responsibilities (employment, children, partner), meaningful activities (Best et al, 2016), and the perceived health, legal and financial risks associated with ATS were foregrounded and became allied with critical turning points out of ATS use.…”
Section: Discussionmentioning
confidence: 99%
“…These instances of successful integration, marrying morality with taste, creates an “alternative hedonism.” Alternative hedonism describes a type of eudaimonic well‐being, involving fulfillment of one's virtuous potentials and expressing who one really is (Deci & Ryan, 2008; Soper, 2007). This type of well‐being is compatible with sustainable consumption activities and might, in theory, allow consumers to avoid the experience of sacrifice (Caruana et al, 2020). Alternative hedonism, though, might be confined to consumers with a strong sense of morality.…”
Section: Discussionmentioning
confidence: 99%
“…<…> The genre, together with reality, falls into the factual entertainment category, and programs are most often didactical at their core and give practical advice and inspiration on food, fashion, body, garden and house, all of which are phenomena through which we express and develop our identities" ( [15], p. 38). As a result, a phenomenon develops, which researchers (Kate Soper, Lyn Thomas, Robert Caruana, Sarah Glozer, Giana M. Eckhardt [32][33][34]) refer to as "alternative hedonism": "'Alternative hedonism' is here theorized as an immanent critique of 'consumerism' , and the impulse behind a new 'political imaginary' or vision of the 'good life' that might influence (along with other developments) the move to a more socially just and environmentally sustainable and enjoyable future" ( [33], p. 1). This phenomenon is directly related to the genres of reality: "In lifestyle television we identified four sub-genres where the representation of the joys of consumption is tempered by anxieties about quality of life, and desires for other pleasures: narratives of 'relocation' from urban noise and pollution to rural community and natural beauty; cookery programmes focusing on quests for authentic, wild or local food; programmes focusing on spiritual journeys motivated by disillusionment with material success; and finally, 'ecoreality' programmes, where the protagonists are challenged to adopt a new and 'greener' lifestyle" ( [33], p. 2).…”
Section: Lightweight and Simplified Truth And Mass Media's Creation Omentioning
confidence: 99%